Using automated text messages to monitor adverse events following immunisation in general practice - Leeb, A.; Regan, Annette; Peters, I.; Leeb, C.; Leeb, G.; Effler, P. (Australasian Medical Publishing, 2014)
Objective: To assess the performance of SmartVax, a prototypic active monitoring system for adverse events following immunisation (AEFI) using short message service (SMS) text messages and clinical data extracted from commercially available medical practice management software. Design, setting and participants: Between 11 November 2011 and 10 June 2013, adult patients and parents of paediatric patients receiving routine vaccinations in general practice were sent an SMS by SmartVax enquiring if they had experienced any AEFI and requesting a reply by SMS. Attempts were made to telephone patients who did not reply by SMS. Main outcome measures: The proportion of patients sent an SMS who replied by SMS, and the proportion of respondents indicating possible AEFI. Results: Of 3281 vaccinated patients, 3226 (98.3%) had a mobile telephone number on record and were sent an SMS. Of 2342 patients (72.6%; 95% CI, 70.0%-75.1%) who responded by SMS, 264 (11.3%; 95 CI, 9.9%-12.7%) reported possible AEFI. The response rate was = 70% for both paediatric and adult patients. Eighty-per cent of SMS replies were received within 2 hours of transmission of the query SMS. There was no significant difference in the proportion reporting possible AEFI between patients who replied by SMS and those who did not respond by SMS but were subsequently contacted by a telephone call (P = 0.99). Conclusions: More than 70% of patients responded by SMS to an SMS query about whether they had any vaccine reactions, with the data received in near real-time. Active surveillance of AEFI using SMS has the capacity to complement existing passive reporting systems, potentially permitting more rapid identification of emerging safety signals.